2018
DOI: 10.1371/journal.pone.0192884
|View full text |Cite
|
Sign up to set email alerts
|

In vitro mouse spermatogenesis with an organ culture method in chemically defined medium

Abstract: We previously reported the successful induction and completion of mouse spermatogenesis by culturing neonatal testis tissues. The culture medium consisted of α-minimum essential medium (α-MEM), supplemented with Knockout serum replacement (KSR) or AlbuMAX, neither of which were defined chemically. In this study, we formulated a chemically defined medium (CDM) that can induce mouse spermatogenesis under organ culture conditions. It was found that bovine serum albumin (BSA) purified through three different proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 33 publications
(44 reference statements)
3
34
0
Order By: Relevance
“…It was classified into 6 grades, 0‐5, based on the expression area: 0, ~20, ~40, ~60, ~80, and‐100%, respectively. This GFP grading scale faithfully corresponded to spermatogenic progression, as confirmed in previous studies . To identify haploid cells with an acrosome cap structure, cultured tissues were observed with an inverted microscope applying the GFP‐excitation light (Olympus IX 73; Olympus).…”
Section: Methodssupporting
confidence: 59%
See 2 more Smart Citations
“…It was classified into 6 grades, 0‐5, based on the expression area: 0, ~20, ~40, ~60, ~80, and‐100%, respectively. This GFP grading scale faithfully corresponded to spermatogenic progression, as confirmed in previous studies . To identify haploid cells with an acrosome cap structure, cultured tissues were observed with an inverted microscope applying the GFP‐excitation light (Olympus IX 73; Olympus).…”
Section: Methodssupporting
confidence: 59%
“…As for evaluation, GFP expression extent overall in each tissue was used. Specifically, the cultured tissues were recorded as photograph every week and the proportion of GFP‐expressing region in each tissue was estimated and classified into 6 grades: 0, ~20, ~40, ~60, ~80, and ~100% . Contrary to the control of AG, whose central area usually lacked GFP expression, samples in the PC groups showed GFP expression rather uniformly throughout the whole tissue in many cases, although the central area is yet weaker in GFP (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because KSR was supposed to contain AlbuMAX, the reason of the success was attributable to AlbuMAX. We have further showed that AlbuMAX, but not other popular bovine serum albumin (BSA), has such a strong effect to induce and maintain spermatogenesis . In addition, another BSA product, purified by chromatographic method like the preparation of AlbuMAX, also has a similar effect.…”
Section: Organ Culture Method Modern Developmentmentioning
confidence: 99%
“…We have further showed that AlbuMAX, but not other popular bovine serum albumin (BSA), has such a strong effect to induce and maintain spermatogenesis. 33 In addition, another BSA product, purified by chromatographic method like the preparation of AlbuMAX, also has a similar effect. Thus, we speculate that chromatography purified BSAs contain some important factors effective for in vitro spermatogenesis.…”
Section: Serum Replacement Changed the Scenementioning
confidence: 99%